Essential Electronic Marketing Skills Needed by Rural Farmers in Agrarian Communities for Alleviating Middlemen Profiteering - Babalulu , Madu-Saba Muhammadu; Anorue, Honesta Chidiebere; Amusa, Taofeeq Ade; Moghalu , Favour Amarachi; Ugwoke, Ernest O. (ARRUS Journal of Social Sciences and Humanities, 2025)
This study identified the essential e-marketing skills needed by farmers to reduce middlemen profiteering in agrarian communities. The study followed three research questions and tested three null hypotheses at the 0.05 level of significance. The industry approach functioned and supported the action group design. The population for the study was 107, comprising 55 lecturers, 31 instructors, and 21 mobile money operators. The researchers collected data using a structured questionnaire. Three experts validated the instrument and used the Cronbach alpha reliability method to assess the internal consistency of the questionnaire items. One hundred and seven copies of the instrument were administered, and 91 copies (85 percent) were returned. Weighted mean and standard deviation were used to answer the research questions, while analysis of variance (ANOVA) was used to test the null hypotheses at the 0.05 level of significance. The study found that the rural farmers needed essential skills in operating electronic devices, e-communication, and mobile phone skills. It was recommended that the identified essential electronic marketing skills be packaged and utilised to train rural farmers to improve their e-marketing strategy toward profit maximisation.